1998
DOI: 10.1590/s0100-879x1998000300011
|View full text |Cite
|
Sign up to set email alerts
|

Signaled two-way avoidance learning using electrical stimulation of the inferior colliculus as negative reinforcement: effects of visual and auditory cues as warning stimuli

Abstract: The inferior colliculus is a primary relay for the processing of auditory information in the brainstem. The inferior colliculus is also part of the so-called brain aversion system as animals learn to switch off the electrical stimulation of this structure. The purpose of the present study was to determine whether associative learning occurs between aversion induced by electrical stimulation of the inferior colliculus and visual and auditory warning stimuli. Rats implanted with electrodes into the central nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
3
5
0
2
Order By: Relevance
“…The brain stimulation was applied at a current intensity 5% below the escape threshold previously determined in the open field. The adequacy of this current intensity level for the escape response was verified on the basis of a previous study from this laboratory (Melo et al, 1992;Brandão et al, 1997;Troncoso et al, 1998).…”
Section: Apparatusmentioning
confidence: 92%
See 2 more Smart Citations
“…The brain stimulation was applied at a current intensity 5% below the escape threshold previously determined in the open field. The adequacy of this current intensity level for the escape response was verified on the basis of a previous study from this laboratory (Melo et al, 1992;Brandão et al, 1997;Troncoso et al, 1998).…”
Section: Apparatusmentioning
confidence: 92%
“…Latent inhibition has been considered as a model for information filtering processesand demonstrates attentional processes in rats that are responsive to drug treatment in a fashion that parallels drug responses seen in humans with schizophrenia (Makintosh, 1975;Lubow et al, 1982;Dunn et al, 1993;Sandner et al, 2002). We have already shown that stimulation of neural circuits in the central nucleus of the IC supports Pavlovian conditioning and that latent inhibition may be demonstrated using stimulation of these neural circuits in the IC as negative reinforcement Troncoso et al, 1998;Castilho and Brandão, 2001).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Alguns resultados obtidos de experimentos utilizando o paradigma do comportamento operante, no qual os animais se engajam em tarefas que permitem interromper ou desligar a estimulação elétrica do CI (switch-off) nos permitem afirmar a natureza aversiva deste tipo de estímulo, assim como a característica defensiva da resposta (Melo et al, 1992;Brandão et al, 1997 et al, 1980;1993;1994;Melo et al, 1992;Coimbra & Brandão, 1993;Melo & Brandão, 1995b;Maisonnette et al, 1996;Troncoso et al, 1998;Pandóssio & Brandão, 1999;Pandóssio et al, 2000;Cuadra et al, 2000;Castilho & Brandão, 2001;Lamprea et al, 2002;Macedo et al, 2002). A administração local de benzodiazepínicos ou agonistas GABAérgicos (Melo et al, 1992;Pandóssio & Brandão, 1999) e agonistas ou bloqueadores da recaptação de 5-HT (Melo & Brandão, 1995b) aumenta significativamente os limiares aversivos de estimulação elétrica e a latência para a resposta de "switch-off" dessa estimulação.…”
Section: Có óR Rt Te Ex X D Do or Rs Sa Al Lunclassified
“…Como o CI está primariamente envolvido com o processamento da informação auditiva, isto pode ser importante no processamento da informação acústica de natureza aversiva como, por exemplo, utilizar um som como reforço condicionado negativo (Brandão et al, 1997;Troncoso et al, 1998). Tem sido proposto que neurônios do CI são filtros para sons que precisam de ações imediatas, como certos sons emitidos por presas e predadores (Casseday & Covey, 1996 Brandão et al, 2001;Sandner et al, 2002).…”
Section: DI Is Sc Cu Us Ss Sã ãO Ounclassified